Molecular CHARacterization of capsularpolysaccharide genes and their role in virulenceof klebsiella pneumoniae isolates inhospitalized patients in Egypt - Maha Magdi Mohamed elBastawisie; Mona Wassef (2022)
(3aj GdSfhGJ GdCNjQI , XgQJ (BKlebsiella pneumoniae (hvKp) (3TOjOI GdVQGhI HGYJHGQgG GdeeQV ETcGdjI ddZGjI(B. (3YhGed GdahYI eSdMI HebGheI eJYOOI ddCOhjI GdeMOOGJ aj (BhvKp (3ebdbI ddZGjI(B. (3JgOa gPg GdOQGSI Edi aMU LjfGJ ebGheI GdeVGOGJ GdMjhjI , eeKd eMOOGJ GdahYI Hjf (B100 (3cdaf(B. pneumoniae (3eY GdJQcjR Ydi CfhGY GdeMaXI ef GdYRdGJ bjO GdeMGhdI ddcTa Yf Cj YdGbI Hjf NUGFU GdeVGOGJ GdMjhjI hGdeeKd YhGed GdNWhQI(B. (3Je GdcTa Yf GddRhLI GdeaQWI Yf WQjb ELQGA GNJHGQ GdSdSdI(B. (3Gd Je aMU edaGJ JYQja eVGOGJ GdejcQhHGJ Yf WQjb WQjbI GfJTGQ GdbQU dcd efgG eVGOGJ MjhjI(B. (3Je GSJNOGe (BMIC (3dGNJHGQ bGHdjI chdjSJjf(B. ESBL (3GdfeW GdXGgQj Je GNJHGQ GdEfJGL Yf WQjb GNJHGQ JBRQ GdbQU GdeROhL(B. (3CNjkQG , JVNje (BPCR (3d` (B(wzy_K1 (3h (Bwzy_K2 (3h (Bwzy_K5 (3h (BrmpA (3h (BrmpA2 (3h (BiutA (3h (BiroN (3h (BIncHI1B (3HdGRejO(B) (3h Je ELQGA (B(NDM (3, (BOXA-48 (3, (BKPC (3, (BCTX-M-15 (3, (BVIM (3, (BIMP (3, (BSPM). (3cd Gd cGfJ GdYRdGJ GdeSJYGOI ebGheI ddCOhjI GdeJYOOI (B(100(3%(B) (3hdcf LejYgG cGfJ cPdc YQVI ddJjLjSjcdjf hGdchdjSJjf , (B83(3% efge ebGheI ddejQhHjfje(B. (3cGf (BIsolate K2 (3gh GdfhY GdcHShdj GdhMjO GdPj Je GcJTGag aj eLehYJfG(B.s
Thesis (M.Sc.)-Cairo University-Faculty of Pharmacy,2022.
Bibliography: p. 81-112.
Keywords: Microbiology; Virulence